2016
DOI: 10.1111/plb.12435
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide emission from bamboo culms

Abstract: Bamboos are one of the fastest growing plants on Earth, and are widely considered to have high ability to capture and sequester atmospheric carbon, and consequently to mitigate climate change. We tested this hypothesis by measuring carbon dioxide (CO2 ) emissions from bamboo culms and comparing them with their biomass sequestration potential. We analysed diurnal effluxes from Bambusa vulgaris culm surface and gas mixtures inside hollow sections of various bamboos using gas chromatography. Corresponding variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The Pacific BioSciences (PacBio) sequencing platform, a single‐molecule sequencing technology, offers great improvement over current second‐generation sequencing (SGS) technologies on read lengths (Rhoads and Au, ) and avoids the transcriptome assembly that is required for SGS (Steijger et al ., ). Recently, single‐molecule sequencing technology has been used to characterize the complexity of transcriptome in Salvia miltiorrhiza (Xu et al ., ), Z. mays (Wang et al ., ), Fragaria vesca (Li et al ., ) and Sorghum bicolor (Abdel‐Ghany et al ., ), but not yet in bamboo (Zachariah et al ., ). The draft genome of bamboo has been built and 31 987 protein‐coding genes have been annotated (Peng et al ., ), which makes it an ideal system for investigating the mechanism of fast growth in the plant.…”
Section: Introductionmentioning
confidence: 97%
“…The Pacific BioSciences (PacBio) sequencing platform, a single‐molecule sequencing technology, offers great improvement over current second‐generation sequencing (SGS) technologies on read lengths (Rhoads and Au, ) and avoids the transcriptome assembly that is required for SGS (Steijger et al ., ). Recently, single‐molecule sequencing technology has been used to characterize the complexity of transcriptome in Salvia miltiorrhiza (Xu et al ., ), Z. mays (Wang et al ., ), Fragaria vesca (Li et al ., ) and Sorghum bicolor (Abdel‐Ghany et al ., ), but not yet in bamboo (Zachariah et al ., ). The draft genome of bamboo has been built and 31 987 protein‐coding genes have been annotated (Peng et al ., ), which makes it an ideal system for investigating the mechanism of fast growth in the plant.…”
Section: Introductionmentioning
confidence: 97%
“…Many studies in the past decade have shown the potential of bamboo forests as a carbon sink (a process that removes carbon dioxide from the atmosphere) [6][7][8][9][10][11]. Nevertheless, there remains considerable debate whether bamboo forest ecosystems are a carbon sink or a carbon source (a process of releasing carbon dioxide to atmosphere) [12][13][14]. One possible reason for this uncertainty is insufficient knowledge regarding carbon loss via CO 2 emissions from bamboo forests [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there remains considerable debate whether bamboo forest ecosystems are a carbon sink or a carbon source (a process of releasing carbon dioxide to atmosphere) [12][13][14]. One possible reason for this uncertainty is insufficient knowledge regarding carbon loss via CO 2 emissions from bamboo forests [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is still difficult to determine whether the bamboo forest ecosystem is a carbon sink or a carbon source (Koike et al 2001;Dü king et al 2011;Zhou et al 2011). One of the possible reasons for the difficulty is insufficient knowledge about the ecosystem respiration of bamboo forests (Zachariah et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Bamboo forests release CO 2 into atmosphere through respiration in the culm, leaves, branches and soil including roots (Isagi 1994;Isagi et al 1997;Liu et al 2011;Hsieh et al 2016;Zachariah et al 2016). Among these, culm respiration (R C ) is a fundamental component of carbon cycling in bamboo forests (Isagi 1994;Isagi et al 1997).…”
Section: Introductionmentioning
confidence: 99%